Case Report: Two cases of non-small cell lung cancer with coexistence of NTRK2 fusion and EGFR mutations - Zhang, Yuping; Zhang, Hengming; Li, Xiufeng (Frontiers in Oncology, 2025)
ObjectiveTo investigate the clinical and pathological characteristics of patients with non-small cell lung cancer exhibiting coexistence of NTRK2 fusion and EGFR mutations.MethodsClinical data, as well as histopathological, immunohistochemical, and molecular pathological characteristics, of two patients harboring both NTRK2 gene fusions and EGFR gene mutations were retrospectively analyzed, and relevant literature was also reviewed.ResultsBoth patients were women aged 57 and 66 years. The two cases were diagnosed as invasive lung adenocarcinoma, and immunohistochemical staining showed that all tumor cells expressed CK7, Napsin A, TTF-1, and PD-L1. In Case 1, an EGFR mutation in the primary lung lesion, coexistence of NTRK2 fusion and EGFR mutation in liver metastases, and concurrent MET gene amplification and FGFR1 gene mutation were observed. In Case 2, the coexistence of NTRK2 fusion and EGFR mutation was detected in the primary lung lesion. The Tumor Mutation Burden (TMB) and microsatellite status were classified as TMB-L and MicroSatellite Stable (MSS), respectively, in both cases. Case 1 received osimertinib combined with savolitinib, had 33 months of follow-up, and achieved a partial response. Case 2 received furmonertinib and achieved a complete response.ConclusionNTRK2 fusion coexisting with EGFR mutations is a rare molecular characteristic of non-small cell lung cancer, accompanied by positive PD-L1 expression, and may serve as a promising biomarker for targeted therapy.